MENUJU HARMONI DALAM KERAGAMAN PERSPEKTIF AL-QUR’AN - Asep Muksin, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
Diversity or diversity is a gift and provision of Allah SWT. for his people to know each other, understand, install and bind. However, the fact is often the trigger for division by mutual hostility and hatred between one another. This research examines in depth about diversity and unity in the perspective of the Qur'an through the narrations of classical and contemporary mufassir. This study uses a thematic-contextual interpretation method that is descriptive in nature. The results of this study indicate that the diversity of religions or beliefs, culture, language, skin color is part of the sunnatullah that must be addressed wisely. The Spirit of the Qur'an emphasizes that the basic principle that must be used as a guide in dealing with this diversity is to precipitate noble values, including mutual respect (at-tasâmuh), mutual assistance (at-ta'âwun), and mutual improvement (at-tasâmuh) mutual love (at-tarahum). This fact refutes the accusations against the Qur’an which considers it a book of hatred and is full of calls for violence.